2015
DOI: 10.4103/2153-3539.158066
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between quantitative digital image analysis and fluorescence in situ hybridization of breast cancer equivocal human epidermal growth factor receptors 2 score 2+ cases

Abstract: Background:Optimization of workflow for breast cancer samples with equivocal human epidermal growth factor receptors 2 (HER2)/neu score 2+ results in routine practice, remains to be a central focus of the on-going efforts to assess HER2 status. According to the College of American Pathologists/American Society of Clinical Oncology guidelines equivocal HER2/neu score 2+ cases are subject for further testing, usually by fluorescence in situ hybridization (FISH) investigations. It still remains on open question, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The evidence identified by our systematic review included studies with reported practices resulting in high concordance rates of QIA HER2 IHC results with FISH test results. 18,23,3335 These studies provide indirect evidence that supports the importance of pathologist oversight of automated QIA results. Importantly, cases with QIA HER2 IHC interpretations that were discordant with FISH test results were explored in some of these studies and highlight issues with QIA that require pathologist oversight and awareness.…”
Section: Resultsmentioning
confidence: 68%
“…The evidence identified by our systematic review included studies with reported practices resulting in high concordance rates of QIA HER2 IHC results with FISH test results. 18,23,3335 These studies provide indirect evidence that supports the importance of pathologist oversight of automated QIA results. Importantly, cases with QIA HER2 IHC interpretations that were discordant with FISH test results were explored in some of these studies and highlight issues with QIA that require pathologist oversight and awareness.…”
Section: Resultsmentioning
confidence: 68%
“…Similar results were obtained by numerous studies that have demonstrated a high degree of correlation between digital image analysis and pathologist visual scoring. The majority of this research has been performed in breast cancer tissue on estrogen receptor, progesterone receptor (Turbin et al, 2008;Faratian et al, 2009;Bolton et al, 2010;Krecsak et al, 2011), human epidermal growth factor receptor (Atkinson et al, 2011;Ayad et al, 2015), Ki 67 assessment in breast cancer (Ayad et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For the interpretation of the FISH, the following cut-off points are used according to the updated recommendations of ASCO/CAP of 2013 on the determination of HER-2 [ 11 ]: ( Figure 3 ).…”
Section: Diagnosesmentioning
confidence: 99%